Effect of Mother Plant Nutrition on Seed Quality of Wheat (Triticum aestivum.L) in Central Terai Region of Nepal - Paneru, Prakash; Bhattachan, Birendra Kumar; Amgain, Lal Prasad; Dhakal, Suman; Yadav, Bisheswar Prasad; Gyawaly, Pankaj (International Journal of Applied Sciences and Biotechnology, 2017)
Seed quality is the major concern for future crop production which largely depends on the nutrient we applied. To evaluate the effect of different doses of nitrogen and phosphorus on yield and seed quality of wheat an experiment was conducted during 2014/15 at agronomy research block of Agriculture and Forestry University. The experiment was designed on randomized complete block experiment with four levels of Nitrogen (0, 50, 100, and 150 kg N/ha) and Phosphorus (0, 25, 50, 75 kg P205/ha) Lab experiment was conducted to evaluate the germination and vigor test of the progeny seeds obtained from the mother plant. Highest grain yield (3.64t/ha) was associated with 100 kg N/ha which was statically similar with 150 kg N/ha, similarly highest grain yield (3.14t/ha) was associated with 75 kg P/ha which was at par with 50 kg P/ha and 25 kg P/ha. Highest germination percentage was associated with 150 kg N/ha (94.08) and 75 kg P/ha (93.66) Highest vigor was observed (36.5) at 100 kg N/ha which was at par with 150 kg N/ha whereas highest vigor was obtained at 50 kg P/ha (35.77) which was at par with 75 kg P/ha (35.71) Gross return, Net return and Benefit Cost ratio was highest at 100 kg N/ha which was at par with 150 kg N/ha. Similarly highest gross return (104.9 thousands) was observed at 75 kg P/ha, highest net income (54.81 thousands), and benefit cost ratio (2.105) was observed with 50 kg P/ha. Therefore for the better yield, good economic return and good seed quality application of nitrogenous fertilizers at 100 kg N/ha and phosphorus at 50 kg P/ha is useful under Chitwan condition.